The prognostic value of Th17/Treg cell in cervical cancer: a systematic review and meta-analysis - Zhang, Jingwei; Zhan, Jijie; Guan, Ziting; Lin, Xinmei; Li, Tian; Li, Miao; Zhang, Changlin; Zhong, Li (Frontiers in Oncology, 2024)
BackgroundThe prognostic significance of Treg and Th17 cells, as well as their ratio (Th17/Treg), in cervical cancer remains a topic of debate. Our study aimed to clarify their association with patient survival and clinical outcomes in cervical cancer through a comprehensive meta-analysis.Materials and methodsWe conducted a comprehensive search in PubMed, Embase, and Web of Science to identify eligible studies. Studies related to cervical cancer and involving Treg cells or Th17 cells were included. For prognostic analysis, we collected Hazard Ratio values of patient survival. For studies focusing on clinical characteristics, we selected mean and standard deviation values for further analysis. This study was registered at PROSPERO (ID:CRD42024546507).ResultsOut of the 2949 records initially retrieved, we ultimately included 21 studies in our analysis. High levels of Treg cells were found to be correlated with shorter survival in patients with cervical cancer. Subgroup analysis revealed that the prognostic effect of Treg cells on cervical cancer was not influenced by their source or definition. However, analyses of different survival measures indicated that only Overall Survival showed a correlation with Treg cell levels. Additionally, Treg cells were associated with clinical staging. High-grade Th17 cells were associated with lymphatic metastases and advanced clinical stage. The Th17/Treg ratio was found to be elevated in both cervical intraepithelial neoplasia and cervical cancer patients compared to controls.DiscussionDespite limitations such as heterogeneity among selected studies and inadequate subgroup analyses, our study contributes to a deeper understanding of the significance of Treg cells in the onset and progression of cervical cancer. It also provides valuable insights for future research in immunotherapy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024546507.